Effect of Different Positions of Pregnant Women on their Comfort and Fetal Cardiotocographic Patterns During Non Stress Test - Essa, Rasha Mohamed; Hafaz, Samar K. (International Journal For Research In Health Sciences And Nursing, 2018)
Background: Non-stress test (NST) is part of a routine monitoring of pregnant women before delivery and it is often used early in pregnancy. A variety of positions can be used during non - stress test, such as semi fowler's, lateral tilts, lateral recumbence, supine and semi fowler's with tilts. Many researches are needed to confirm which position is the best to be used during NST. The current study aims to determine the effect of different maternal positions on pregnant women's comfort and fetal cardiotocographic patterns during Non -Stress Test .. Methods: Quasi-experimental design was utilized. A convenience sample of 90 pregnant women who attended the antenatal clinic at Elshatby Maternity University Hospital in Alexandria governorate. Subjects were non randomly equally divided into three groups:-Group I (study 1): left lateral position group (30) participants. Group II (study 2): semi-fowler’s position group (30) participants. Group III (control): supine position group (30) participants. Three tools were used for data collection. Tool one: Socio-demographic data and reproductive history structure interview schedule. Tool two: Non stress test recording sheet, Tool three: Visual Analog Discomfort Scale (VADS):-Study results revealed that there was a statistically significant differences in the results of non- stress test reactivity among groups using supine , left lateral and semi -fowler positions. Where, the left lateral position was associated with more non stress test reactivity than semi –fowler and supine positions. The study concluded Pregnant women who are placed in left lateral position during non- stress test exhibit more comfort and more fetal non stress test reactivity than those placed in supine and semi-fowler’s positions. The study recommended A simple protocol for NST application need to be developed to be followed during the test and, Integrating non – stress test into nursing student’s curriculum.